Analisis Dampak Penerapan IT Terhadap Proses Pembukaan Rekening Tabungan Di Bank Muamalat KCP Pasuruan - Konita Mardia; Saiful Bakhri; Ilham Wahyudi (Universitas Nahdlatul Ulama Pasuruan, Indonesia, 2024)
Currently, it can be said that almost all banks in Indonesia have mobile banking applications to suit the lifestyle of their customers, including Bank Muamalat by launching a mobile banking application (Muamalat DIN). So in this research the researcher will discuss the impact of implementing IT (Mobile Banking) to find out what impacts it has had on customers and companies, where this research was carried out using qualitative methods, namely field research using primary and secondary data. The impact of implementing IT is very significant on the customer opening process, one of which is being able to provide direction or understanding to access various banking services at any time 24 hours a day and this also has a positive effect on the company